PENGARUH MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN GEOGRAFI DI SMA NEGERI 4 BUKITTINGGI - Aldyanti, Dinda; Novio, Rery (JURNAL BUANA, 2024)
The research aims to analyze the influence of the student facilitator and explaining learning model on critical thinking skills in geography learning at SMA N 4 Bukittinggi. The method of this study uses a quasi-experimental. Data collection techniques used are observation and documentation. The result of the t test analysis obtained a significance value of 0,00 < 0,05 dan Tcount > Ttable 6,166 > 1,66723. The result of the N Gain test, the average pretest and posttest score for the control class was 55,29% with the criteria being less affective and the average score for the pretest and posttest for the experimental class was 68,11% with the criteria being quite affective. The results of the research on critical thinking skills in the control class were 77,708 in the good category, while the experimental class was 86,367 in the very good category. Thus, there is an affect of using the student facilitator and explaining model on students critical thinking skills.